Letters to a Young Pharmacist : Even More Sage Advice on Life and Career. - Cantrell, Susan A. (American Society of Health-System Pharmacists, 2022)
Letters to a Young Pharmacist is the next installment of the ASHP Letters series created to inspire pharmacists through all stages of their professional journey.
Description based upon print version of record.
Keywords: Pharmacy -- Vocational guidance.; Pharmacists -- United States -- Correspondence.; Pharmacie -- Orientation professionnelle.; Pharmaciens -- États-Unis -- Correspondance.; Pharmacists; Pharmacy -- Vocational guidance; United States; Personal correspondence